Plant and Animal Based Composites - Anitha, Akkireddy; Anitha, Akkireddy; B. Sridhar, Babu; B. Sridhar, Babu; Chikesh, Ranjan; Chikesh, Ranjan; Davim, J. Paulo; Davim, J. Paulo; Deepa, Kodali; Deepa, Kodali; F. M., Mwema; F. M., Mwema; et al. (Advanced composites ;, 2021)
The increasing demand for environmentally friendly materials and the need for cheaper fibres points the search in the direction of natural products such as bark, leaves, scales or shells. The aim of this book is to provide a forum to review the recent advances in the area of plant and animal-based composites and identify possible trends for further developments.